Can Postal Networks Advance Financial Inclusion in the Arab World? - El-Zoghbi, Mayada; Martinez, Meritxell (Washington, DC: World Bank, 2012)
As existing and trusted institutions with large branch networks reaching rural areas, Arab postal networks have the potential to be powerful tools in the fight for greater financial inclusion in the Arab world. Beyond a few success stories, however, the Arab world has so far not capitalized on the potential of its postal networks. This is a glaring omission in light of demographic trends that highlight the need for financial access: growing population, high fertility rates, large youth and rural populations, and recent political changes as a result of the Arab spring.